2007
DOI: 10.1210/en.2007-0618
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Quercetin Regulates Growth and Gene Expression in Rat FRTL-5 Thyroid Cells

Abstract: Quercetin is the most consumed flavonoid present in fruits and vegetables. There has been increased interest in the possible health benefits of quercetin and other flavonoids. Because it is reported that these compounds have some antithyroid properties, we were interested whether, and by what mechanism, quercetin might regulate thyroid cell growth and function. In this report we show that quercetin inhibits thyroid cell growth in association with inhibition of insulin-modulated phosphatidylinositol 3-kinase-Ak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 59 publications
(68 reference statements)
2
31
0
1
Order By: Relevance
“…2-fold respectively; Fig. 4), consistent with the previous observations with LY294002 (Garcia & Santisteban 2002, Giuliani et al 2007. These data indicate that PI-103 induces the expression of Nis mRNA, but not iodide uptake.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…2-fold respectively; Fig. 4), consistent with the previous observations with LY294002 (Garcia & Santisteban 2002, Giuliani et al 2007. These data indicate that PI-103 induces the expression of Nis mRNA, but not iodide uptake.…”
Section: Resultssupporting
confidence: 91%
“…The present study and some previous reports (Garcia & Santisteban 2002, Giuliani et al 2007) indicated that these PI3K inhibitors, including PI-103, significantly induced the Nis mRNA expression. PI-103 likely inhibits the translation and/or post-translational regulation of NIS.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These free radicals crop up biologically in the body [4] and have the ability to destroy cell membranes, aggravate the aging process, interrelate with inherent substances and also lead to a number of ailments such as heart disease [5] and cancer [6]. Hence, antioxidants [7] like quercetin are able to counteract the free radicals [8] and help in lessening and also preventing the damages caused by them. It has been found that quercetin has the potential to become an effective remedy for prevention and treatment of several disorders [9].…”
Section: Introductionmentioning
confidence: 99%